2022
DOI: 10.23887/jlls.v5i1.48533
|View full text |Cite
|
Sign up to set email alerts
|

E-Scrapbook: The Needs of HOTS Oriented Digital Learning Media in Elementary Schools

Abstract: The adaptation of new habits after the COVID-19 pandemic has an impact on the lack of availability of learning media that can be used to support the learning process. The role of learning media is very important in the learning process, one of which is to facilitate students in practicing higher-order thinking skills as one of the 21st century skills that must be possessed by students. This study aims to analyze the needs and explore the role of teachers in the process of developing digital learning media cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 25 publications
1
32
0
1
Order By: Relevance
“…Based on these general objectives, it can be seen that the purpose of developing e-modules is that students can master the concept of sociology especially the concept of social groups. The words 'will be able to' in the formulation of general learning objectives indicate the abilities that students will acquire after studying sociology Antara & Dewantara, 2022). To achieve the general goal, namely the analysis of the relationship between social groups that occur in Indonesian society, several main ideas are developed to support this goal, namely the concept of social groups, the concept of social problems, the concept of social equality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these general objectives, it can be seen that the purpose of developing e-modules is that students can master the concept of sociology especially the concept of social groups. The words 'will be able to' in the formulation of general learning objectives indicate the abilities that students will acquire after studying sociology Antara & Dewantara, 2022). To achieve the general goal, namely the analysis of the relationship between social groups that occur in Indonesian society, several main ideas are developed to support this goal, namely the concept of social groups, the concept of social problems, the concept of social equality.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in understanding the concept of sociology are also supported by the limitations of learning resources that can be used by students. Learning resources are anything that can be used to facilitate student learning, help students achieve learning goals and improve student learning processes (Antara & Dewantara, 2022;Asrial et al, 2019). Students do not have independent learning resources that can broaden their horizons about learning concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by IKAPI (Indonesian Publishers Association) in 2015 stated that the book publishing industry in Indonesia no longer reaches 100%, only 80%, because 20% of that part has been converted into the e-book market (electronic book), the market changes. This also indicates that the transition from conventional books to e-books is still ongoing in Indonesia and will continue to grow (Antara & Dewantara, 2022;Suryaningtyas et al, 2020). Previous research revealed that interest is a tendency of the heart towards something, while reading is spelling, reciting and understanding the content of writing (Mahayanti et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…One form of media that can be developed based on the results of the needs analysis is E-Scrapbook. E-Scrapbook media is a digital-based learning media in the form of an electronic book (e-book) that contains information or explanations related to learning materials presented with pictures/decorations that can attract the attention of students and make it easier for them to understand the learning material (Antara & Dewantara, 2022;Wusqo et al, 2021). E-Srapbook learning media can be integrated by including HOTS questions at the end of each learning topic.…”
Section: Introductionmentioning
confidence: 99%